Thyroid hormone analogs for the treatment of dyslipidemia: past, present, and future - Delitala, Alessandro P.; Delitala, Giuseppe; Sioni, Paolo; Fanciulli, Giuseppe (Current medical research and opinion, 2017)
Objective: Treatment of dyslipidemia is a major burden for public health. Thyroid hormone regulates lipid metabolism by binding the thyroid hormone receptor (TR), but the use of thyroid hormone to treat dyslipidemia is not indicated due to its deleterious effects on heart, bone, and muscle. Thyroid hormone analogs have been conceived to selectively activate TR in the liver, thus reducing potential side-effects. Methods: The authors searched the PubMed database to review TR and the action of thyromimetics in vitro and in animal models. Then, all double-blind, placebo controlled trials that analyzed the use of thyroid hormone analog for the treatment of dyslipidemia in humans were included. Finally, the ongoing research on the use of TR agonists was searched, searching the US National Institutes of Health Registry and the WHO International Clinical Trial Registry Platform (ICTRP). Results: Thyromimetics were tested in humans for the treatment of dyslipidemia, as a single therapeutic agent or as an add-on therapy to the traditional lipid-lowering drugs. In most trials, thyromimetics lowered total cholesterol, low-density lipoprotein cholesterol, and triglycerides, but their use has been associated with adverse side-effects, both in pre-clinical studies and in humans. Conclusions: The use of thyromimetics for the treatment of dyslipidemia is not presently recommended. Future possible clinical applications might include their use to promote weight reduction. Thyromimetics might also represent an interesting alternative, both for the treatment of non-alcoholic steatohepatitis, and type 2 diabetes due to their positive effects on insulin sensitivity. Finally, additional experimental and clinical studies are needed for a better comprehension of the effect(s) of a long-term therapy.